Microbial diversity, autotrophic- and heterotrophic processes in Mn-rich marine sediments - Sebastian Silva-Solar; Marit R. van Erk; Gilad Antler; Katrin Knittel; Subhayit Basu; Dirk de Beer (Frontiers in Marine Science, 2025)
Marine microbial ecology aims to link microbial communities to the geochemical processes they drive. Molecular techniques have provided a view of the huge complexity of microbial communities and their metabolic potential, however, the information these approaches give about the geochemical processes is limited. Here, we combined geochemical and 16S rRNA amplicon sequencing analyses to spatially link dominant microbial taxa with geochemical processes in deep-sea sediments of the Gulf of Aqaba. The fine-grained aeolian sediments are diffusion controlled, allowing precise localization of the stratified geochemical processes in well-defined zones by transport-reaction modeling. Geochemical depth profiles and fluxes showed aerobic heterotrophy, nitrification, aerobic Mn-oxidation, denitrification, and anaerobic Fe oxidation to occur in sequence from upper to deeper sediment layers. Although chemoautotrophic processes were significant, 90% of the redox processing was driven by heterotrophy on organic carbon input. The microbial community composition also showed a clear stratification. The oxic zone was dominated by typical aerobes, while anaerobes were largely absent, as expected. Remarkably, the anoxic zone was inhabited by many aerobic bacteria, in addition to the anaerobic community. A narrow brown band enriched in solid-phase Mn-oxide was observed at 2-3 cm depth, where downward diffusing O 2 and upward diffusing Mn 2+ overlapped. Here, members of the family Ca . Scalinduaceae peaked, suggesting involvement in Mn oxidation or -reduction. Dominant families above the band were Woeseiaceae , Nitrospiraceae , and Nitrosococcaceae , whereas below the band Desulfosarcinaceae , Desulfatiglandaceae , Methylomirabilaceae , and Anaerolineaceae dominated. While Ca. Scalinduaceae peaked in the Mn-oxide band, none of the other dominant families were exclusively linked to zones with specific geochemical processes. Our approach did not resolve relations between the geochemical processes and the dominant members of the community unambiguously, but characterized a unique habitat and leads to the formulation of new hypotheses, including the occurrence of cryptic cycling.